1995
DOI: 10.1128/mcb.15.6.3301
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Regulation of Cyclin A Gene Expression by the Cyclic AMP-Responsive Transcription Factors CREB and CREM

Abstract: Cyclin A is a pivotal regulatory protein which, in mammalian cells, is involved in the S phase of the cell cycle. Transcription of the human cyclin A gene is cell cycle regulated. We have investigated the role of the cyclic AMP (cAMP)-dependent signalling pathway in this cell cycle-dependent control. In human diploid fibroblasts (Hs 27), induction of cyclin A gene expression at G 1 /S is stimulated by 8-bromo-cAMP and suppressed by the protein kinase A inhibitor H89, which was found to delay S phase entry. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
184
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(196 citation statements)
references
References 57 publications
11
184
1
Order By: Relevance
“…The markedly transient induction of ICER protein following PH, which di ers from that observed in other systems (Lalli and Sassone-Corsi, 1995;Monaco et al, 1995), may suggest a distinct function. We have recently described the involvement of CREM gene products in the regulation of cyclin A gene and possibly cell cycle (Desdouets et al, 1995). In addition, ablation of the CREM gene in the mouse germline by homologous recombination results in an arrest of postmeiotic male germ cell di erentiation and an increase in apoptosis (Nantel et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The markedly transient induction of ICER protein following PH, which di ers from that observed in other systems (Lalli and Sassone-Corsi, 1995;Monaco et al, 1995), may suggest a distinct function. We have recently described the involvement of CREM gene products in the regulation of cyclin A gene and possibly cell cycle (Desdouets et al, 1995). In addition, ablation of the CREM gene in the mouse germline by homologous recombination results in an arrest of postmeiotic male germ cell di erentiation and an increase in apoptosis (Nantel et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The use of an alternative promoter (P2) lying near the 3' end of the gene, generates the cAMP-inducible repressor isoform ICER (Inducible cAMP Early Repressor) . Elevated ICER expression is characteristic of neuroendocrine tissues (SassoneCorsi, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Previous data (Stehle et al, 1993) strongly suggest that this inhibition is achieved by direct binding of ICERIIg to the CRE in the c-fos promoter. Moreover we have recently reported that the expression of cyclin A was also regulated by ICER-IIg (Lamas et al, 1997) and cAMP levels (Desdouets et al, 1995). ICER-IIg down-regulated cyclin A RNA expression by binding to the CRE in cyclin A promoter.…”
Section: Icer-iig Halts the Expression Of C-fos Proto-oncogenementioning
confidence: 95%
“…Cyclin A1 is highly expressed in pachytene spermatocytes and required for meiosis, and Cyclin A2 is mostly present in type A spermatogonia, including the SSCs Ravnik and Wolgemuth, 1999). Therefore, like in other cell types, Creb and c-Fos enhance the expression of cyclin A and favors the G1/S cell cycle transition in Gfrα-1 positive spermatogonia (Desdouets et al, 1995;Sunters et al, 2004). Taken together, our studies of the effects of Gdnf on SSCs indicate that multiple signaling pathways are responsible for their self-renewal and maintenance.…”
Section: Ras Signaling Pathwaymentioning
confidence: 99%